2014
DOI: 10.1177/156482651403500410
|View full text |Cite
|
Sign up to set email alerts
|

Food Crop Production, Nutrient Availability, and Nutrient Intakes in Bangladesh: Exploring the Agriculture—Nutrition Nexus with the 2010 Household Income and Expenditure Survey

Abstract: Background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…121,122 At present, Bangladesh's food system is rice centric, and rice contains 67% of Bangladesh's total agricultural output of calcium. 123 Although potential benefits of increased dietary diversity are supported in Bangladesh, 44,100 research has yet to address questions as to how diversification could be practicably brought about in the general population, and policies have not favored such implementation or implementation research.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…121,122 At present, Bangladesh's food system is rice centric, and rice contains 67% of Bangladesh's total agricultural output of calcium. 123 Although potential benefits of increased dietary diversity are supported in Bangladesh, 44,100 research has yet to address questions as to how diversification could be practicably brought about in the general population, and policies have not favored such implementation or implementation research.…”
Section: Commentmentioning
confidence: 99%
“…121,122 At present, Bangladesh’s food system is rice centric, and rice contains 67% of Bangladesh’s total agricultural output of calcium. 123 Although potential benefits of increased dietary diversity are supported in Bangladesh, 44,100 research has yet to address questions as to how diversification could be practicably brought about in the general population, and policies have not favored such implementation or implementation research. Research is needed to determine how supply- or demand-side price controls may increase production and consumption of nutrient dense-foods while reducing that of rice, without spreading hunger, marginalizing local firms, or limiting international trade.…”
Section: Commentmentioning
confidence: 99%
“…Representation was the main concern for Bangladesh, with the dietary data representing only 2 districts in the northern region of the country known for high consumption of rice and poor nutrition status. Results of rice consumption for women were found to be very similar to the per capita consumption estimates (453 g/d) from the 2010 Household Income and Expenditure Survey (HIES) of 12,240 rural households in Bangladesh (23). However, the vitamin A–inadequate intake in the Bangladesh study (93%) was much higher than the reported 61% in the 2010 HIES.…”
Section: Discussionmentioning
confidence: 53%
“…Inadequate food production diversity seems to be a barrier to addressing malnutrition in Bangladesh. The food system in Bangladesh has traditionally focused on rice as the main staple crop [3,21] with some production of other crops such as pulses, vegetables, fruit and oil seeds [21] or non-crop products such as fish (aquaculture), and livestock [3]. Home gardens are also important sources of food consumption and income in rural Bangladesh [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although the country has experienced increased production of nutrient-rich foods, such as meat, milk, aqua products, vegetables and fruit, the growth is not sufficient to meet dietary requirements [23]. While the production of vegetables and fruit is increasing, the produced quantity is insufficient to meet the dietary requirements of the Bangladeshi population [21,23]. Meeting the daily WHO requirements for vegetables and fruit needs either a significant increase in production in the country, or large net imports [23].…”
Section: Introductionmentioning
confidence: 99%